What Drives Variation in Investor Portfolios? Estimating the Roles of Beliefs and Risk Preferences - Egan, Mark; MacKay, Alexander; Yang, Hanbin (Review of Financial Studies, 2026)
We present a portfolio choice demand model that allows for the nonparametric estimation of investors’ (subjective) expectations and risk preferences. Using comprehensive 401(k)-plan-level data from 2009 through 2019, we explore heterogeneity in asset allocations using our empirical framework. We recover investors’ beliefs about each asset and examine the implications and potential sources of those beliefs. Heterogeneity in expectations across investors accounts for twice as much variation in portfolio holdings as heterogeneity in risk aversion. Belief heterogeneity is partly driven by investors’ characteristics and experiences, reflecting local sources of information such as county-level GDP and employers’ past performance.